The multiple intelligences - Checkley, Kathy; Wurzburg, Gerardine (Virginia : Association for Supervision and Curriculum Development, 1995)
Focuses on definition of intelligence, explore and identify the key points of intelligence and multiple intelligence and also describe on the seven intelligences: linguistic, musical, logical -mathematical, spatial, bodily kinesthetic, interpersonal and intrapersonal
part 1. Understanding multiple intelligences - part 2. Classrooms applications - part 3. Creating the school of the future
Videos are accompanied by 1 soundrecording of The multiple intelligences & education : viewpoints with Howard Gardner and 3 books of facilitator's guide
Executive producer, Marcia D'Arcangelo, editor, Judy White ; writer, Kathy Checkley
Narrator: Carroll James
Keywords: Multiple intelligences; Teaching; Learning